The sign: Product of what? About the monstrous complexity of the linguistic sign (Signifiances (Signifying), 2019)
What is the basis of the linguistic sign and what is it made of? It is a question of trying to explain the complexity of this significant mechanism by taking into account its components, without however artificially freezing them, but by emphasizing that the linguistic sign is the product, in becoming, of a multifactorial construction (time, body, learning, interlocutor) and in particular of complex mechanisms of a physiological order, underlying by a cognitive and sensory-motor dimension.